Knowledge of Pharmacy Staff Regarding Over the Counter Medications in Erbil City - Araz Abdulmajid Aziz; Salih Ahmed Abdulla (Hawler Medical University, 2019)
Background and objectives: Use of over the counter (OTC) medications is an important area for research within different health care systems. It is also associated with increased risk of abuse and medication addiction. The need to avoid unnecessary exposure to medication is a concern among the health-care community, in which pharmacy staff plays first line of response and their knowledge is critical. In Kurdistan region of Iraq, other medical and to some extend non-medical staff also works in pharmacies which may affect their scientific understanding of medication. The current study aims to determine the knowledge of pharmacies staff regarding OTC medication use in Erbil city. Methods: A cross-sectional study was conducted from 15th- October 2018 to 15th -October 2019. A sample of 187 pharmacies in Erbil city Centre was recruited through a systematic random sampling technique. Data were collected through direct interview with participants, A questionnaire was used for interviewing the pharmacy staff about socio-demographic characteristics and knowledge regarding OTC medications. The validity and reliability of the instrument was checked. Data were analyzed by using the software system of Statistical Package for Social Science (SPSS version 23). Results: The total number of the studied sample was 187 medical and para-medical staff working in Erbil pharmacies. Their mean age + SD were 28.56 + 5.33 years, ranging from 18 to 45 years. Generally only quarter (25%) of the whole sample had good level of knowledge. less than one third (29.4%) of the sample knew the correct definition of the OTC. Only 28.3% of the sample thinks that the OTC medications mostly cause side effects. Good level of knowledge was significantly associated with being female, and being a graduate and with being a specialized pharmacist. Conclusion: There is a limited knowledge about OTC medications among staff working in pharmacies.